Recognition and characterization of Erythropoietin binding-proteins in the brain of mice - Kowsari, Reza (Iran J Basic Med Sci, 2016)
OBJECTIVE(S): Erythropoietin (EPO), is a 34KDa glycoprotein hormone, which belongs to type 1 cytokine superfamily. EPO involves in erythrocyte maturation through inhibition of apoptosis in erythroid cells. Besides its main function, protective effects of EPO in heart and brain tissues have been reported. EPO has a critical role in development, growth, and homeostasis of brain. Furthermore EPO has great potential in the recovery of different brain diseases which are still under studying. In this research, EPO binding pattern to brain proteins in animal model was studied. MATERIALS AND METHODS: EPO antibody was covalently crosslinked to protein A/G agarose. in order to interact between EPO and its target in brain, about 5µg EPO added to brain homogenates(500ul of 1 mg/ml) and incubate at 4ο C for 30 min. brain tissue lysate were added to agarose beads, After isolation of target proteins(EPO - protein) both one and two-dimensional gel electrophoresis were performed. Proteins were identified utilizing MALDI-TOF/TOF and MASCOT software. RESULTS: This research showed that EPO could physically interact with eightproteins including Tubulin beta, Actin cytoplasmic 2, T-complex protein 1, TPR and ankyrin repeat-containing protein 1, Centromere-associated protein E, Kinesin-like protein KIF7, Growth arrest-specific protein 2 and Pleckstrin homology-like domain family B member 2. CONCLUSION: Since EPO is a promising therapeutic drug for the treatment of neurological diseases, identified proteins may help us to have a better understanding about the mechanism of protective effects of EPO in the brain. Our data needs to be validated by complementary bioassays.